Fleksibilitas Kognitif sebagai Prediktor Pikiran Bunuh Diri pada Mahasiswa Tingkat Akhir - Yoseph Chrisna Laiyan; Adelina Rahmawati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study investigates the role of cognitive flexibility as a protective factor against suicidal ideation among final-year undergraduate students in Central Java. Grounded in the Fluid Vulnerability Theory and the Suicidal Mode framework, this research examines how internal cognitive mechanisms regulate the activation of suicide-related affective systems under academic stress. A correlational quantitative design was employed, involving 252 participants selected through purposive sampling. Data were collected using the Cognitive Flexibility Inventory (CFI) and the Revised Suicide Ideation Scale (R-SIS), both of which demonstrated strong psychometric properties. Linear regression analysis revealed a significant negative relationship between cognitive flexibility and suicidal ideation (Î² = -0.179, p < .01), indicating that the higher cognitive flexibility predicts lower levels of suicidal thoughts. Furthermore, cognitive flexibility significantly reduced both covert (passive desire) and overt (active planning) dimensions of suicidal ideation. These findings highlight cognitive flexibility as a transdiagnostic protective mechanism that disrupts the activation of suicidal mode by enabling adaptive cognitive reappraisal and alternative problem-solving strategies. The study contributes to the literature by shifting the focus from external stressors to internal cognitive processes, offering implications for preventive interventions in higher education settings.